(untitled) - Fred Hall (London, 1994)
The book covers the design and installation of gas appliances, oil-firing systems, hot water supply and heating systems. It includes up-to-date references to relevant Bylaws, Regulations and Codes of Practice where applicable. It also provides a comprehensive text supported bt illustrations, tables and calculations. Fianlly, the book reinforces understanding by end-of-chapter test questions
Keywords: heating-pipes,hot-water supply,plumbing